Erratum: Large meta-analysis of genome-wide association studies identifies five loci for lean body mass. Issue 1 (December 2017) - Zillikens, M.; Demissie, Serkalem; Hsu, Yi-Hsiang; Yerges-Armstrong, Laura; Chou, Wen-Chi; Stolk, Lisette; Livshits, Gregory; Broer, Linda; Johnson, Toby; Koller, Daniel; Kutalik, Zoltán; Luan, Jian'an; et al.
A correction to this article has been published and is linked from the HTML version of this article.